Diagnostic performance of the basic and advanced life support termination of resuscitation rules: A systematic review and diagnostic meta-analysis. (1st March 2020) - Nas, Joris; Kleinnibbelink, Geert; Hannink, Gerjon; Navarese, Eliano P.; van Royen, Niels; de Boer, Menko-Jan; Wik, Lars; Bonnes, Judith L.; Brouwer, Marc A.
Abstract: Aim: To minimize termination of resuscitation (TOR) in potential survivors, the desired positive predictive value (PPV) for mortality and specificity of universal TOR-rules are ≥99%. In lack of a quantitative summary of the collective evidence, we performed a diagnostic meta-analysis to provide an overall estimate of the performance of the basic and advanced life support (BLS and ALS) termination rules. Data sources: We searched PubMed/EMBASE/Web-of-Science/CINAHL and Cochrane (until September 2019) for studies on either or both TOR-rules in non-traumatic, adult cardiac arrest. PRISMA-DTA-guidelines were followed. Results: There were 19 studies: 16 reported on the BLS-rule (205.073 patients, TOR-advice in 57%), 11 on the ALS-rule (161.850 patients, TOR-advice in 24%). Pooled specificities were 0.95 (0.89–0.98) and 0.98 (0.95–1.00) respectively, with a PPV of 0.99 (0.99–1.00) and 1.00 (0.99–1.00). Specificities were significantly lower in non-Western than Western regions: 0.84 (0.73–0.92) vs. 0.99 (0.97–0.99), p < 0.001 for the BLS rule. For the ALS-rule, specificities were 0.94 (0.87–0.97) vs. 1.00 (0.99–1.00), p < 0.001. For non-Western regions, 16 (BLS) or 6 (ALS) out of 100 potential survivors met the TOR-criteria. Meta-regression demonstrated decreasing performance in settings with lower rates of in-field shocks. Conclusions: Despite an overall high PPV, this meta-analysis highlights a clinically important variation in diagnostic performance of the BLS and ALS TOR-rules. Lower specificity and PPV were seen in non-Western regions, and populations with lower rates of in-field defibrillation. Improved insight in the varying diagnostic performance is highly needed, and local validation of the rules is warranted to prevent in-field termination of potential survivors.